JeffTargetTestPrep wrote:

AbdurRakib wrote:

If y ≠2xz, what is the value of (2xz + yz)/(2xz – y)?

1) 2x + y = 3

2) z = 2

We can start by simplifying the question:

(2xz + yz)/(2xz – y) = ?

z(2x + y)/(2xz – y) = ?

Statement One Alone:2x + y = 3

Although statement one provides a value for 2x + y, we still do not have a value for z or 2xz –y. Thus, statement one alone is not sufficient to answer the question. We can eliminate answer choices A and D.

Statement Two Alone:z = 2

Although statement two provides a value for z, we still do not have a value for 2xz – y or 2x + y. Thus, statement two alone is not sufficient to answer the question. We can eliminate answer choice B.

Statements One and Two Together:Using statements one and two, we have values for z and 2x + y. However, since we still do not have a value for 2xz - y, we do not have enough information to answer the question.

Answer: E

Hi Jeff,

I understand that statement 1 & 2 alone are not sufficient but I opted for C in this way

From statement 2 we get z=2

denominator becomes 4x-y

=> 2x^2 -1y^2

=> (2x+y) (2x-y)

And numerator becomes 2(2x+y)

2x+y cancels out from both numerator and denominator

now we are left with 2/2x-y

from statement 1 we get 2x+y = 3

=> y=3-2x

putting value of y in 2/2x-y

we get 2/2x-3-2x

which comes up to 2/-3

I know this must be one of the silliest question you have encountered but can`t help myself with this.

your help will be highly appreciated.

Thanks in advance!